Dual-colored 4, 4′, 4′′, 4′′′-(cyclobutane-1, 2, 3, 4-tetrayl)-tetrabenzoate electrochromic materials with large optical contrast and coloration efficiency. (14th August 2019) - Zhu, Chun-rong; Xie, Jia-ping; Mou, Hong-rong; Huang, Zhen-jie; Tang, Qian; Gong, Cheng-bin; Fu, Xiang-kai
Abstract : This paper reports novel ester-containing electrochromic materials, 4, 4′, 4′′, 4′′′-(cyclobutane-1, 2, 3, 4-tetrayl)tetrabenzoate derivatives, with dual-colored electrochromism, high color contrast and coloration efficiency. Abstract : Nine 4, 4′, 4′′, 4′′′-(cyclobutane-1, 2, 3, 4-tetrayl)tetrabenzoate derivative electrochromic materials have been designed, synthesized, and characterized. Seven compounds displayed dual-colored electrochromism. The required potential and colored states were markedly influenced by substitution. When the substituent was alkyl, colored states of purple and blue were obtained at an applied voltage of −2.3 and −2.6 V, respectively; when the substituent was phenyl with an electron-donating group, colored states of purple bluish and bright blue were obtained at an applied voltage of −2.1 and −2.3 V, respectively; when the substituent was phenyl with an electron-withdrawing group, monocolored state and bad electrochromic properties were obtained. Moreover, electrochromic devices based on most of these compounds show large optical contrast, fast response time, and high coloration efficiency.